A Socio-Cognitive Critical Discourse Analysis of Ideological Manipulation in Imran Khan’s Political Interviews - Shahida Bano; Muhammad Azaz Khan; Awais Bin Wasi, (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This study examined particularly four interviews of Imran Khan (The Former Prime Minister of Pakistan), which were being aired on official channels like CNN, Sky Net News, Russian TV and TRT World, observed under the lenses of Socio-Cognitive Approach of van Dijk. The entire analysis focused mainly on cognitive, social and textual dimensions of the due interviews in order to unveil underlying ideological frameworks as well as power. As a result, the overall findings show that Imran Khan's discourse reflects his manipulative political agenda and strategically tends to frame issues to align with his personal political stance as well as governmental means of interests. The study thus enforces the vitality of analyzing textual structures and linguistic in Political discourse, specifically within the contexts of power. While using van Dijk's Model, this research identifies both the micro and the macro level discourse structures. At the Micro Level, the selected interviews are the one that contained (questions, agreements and assertions) as well as the indirect acts in the form of suggestions and implications. Meanwhile, the Macro Level, goes for the discourse that displayed coherent organization through the topic, introduction, argument development, and the conclusion.